Long-Term Kidney Prognosis and Pathological Characteristics of Late-Onset Lupus Nephritis - Tian, Na; Zhou, Qian; Yin, PeiRan; Chen, WenFang; Hong, LingYao; Luo, QiMei; Chen, MengHua; Yu, XueQing; Chen, Wei (Frontiers in Medicine, 2022)
Background Arguments still exist on prognosis of late-onset SLE, especially their kidney function. The purpose of this study was to investigate long-term kidney outcomes in patients with late-onset lupus nephritis (LN). Methods A retrospective long-term cohort study was conducted in adult Chinese patients with LN. The patients were divided into late- (>50 years) and early-onset (<50 years) LN groups. The baseline characteristics, especially the kidney pathological characteristics, were compared. The cohort was followed-up for kidney outcome defined as doubling of serum creatinine or ESRD. Cox regression analysis was used to examine the association between late onset LN and its outcomes. Results A total of 1,264 patients were recruited, who were assigned to late-onset LN with 102 patients and early-onset LN with 1,162 patients. The late-onset LN group showed a worse baseline kidney function and more chronic pathological lesions than the early-onset LN group. During a follow-up time of 55 (3, 207) months, 114 (13.1%) deaths occurred, 107 (12.2%) had doubling of creatinine, and 80 (9.1%) developed end-stage kidney disease. The 5- and 10-year survival rates of the late-onset LN group were 67.6 and 50.5%, respectively, which were much worse than those of the early-onset LN group (89.8 and 84.6%, respectively). However, no significant difference was found on kidney survival (log-rank chi-square = 3.55, p = 0.06). Cox regression analysis showed that late-onset LN was an independent risk factor for patient survival (hazard ratio = 3.03, 95% CI (1.39, 6.58), p = 0.005). Increased baseline serum creatinine was an independent risk factor for kidney survival of patients with late-onset LN. Conclusions Patients with late-onset LN had milder active lesions but severer chronic lesions in kidney pathology. They have poorer overall outcome but relatively favorable kidney outcome. Trial Registration ClinicalTrials.gov Identifier: NCT03001973, 22 December 2016 retrospectively registered.